Traditional natural farming system in the production of Bario rice (Adan rice) by Lun Bawang community in the highland of Borneo, Sarawak, East Malaysia and potential for using biochar, paddy straw and buffalo dung bokashi - Jiwan, Make; Samuel, Henrita; Bulan, Petrus; Abdullah, Nur Ashikin Psyquay; Haruna, Ahmed Osumanu; Wan Yahaya, Wan Asrina; Kundat, Franklin Ragai; Maulana, M. M.; Mustapha, M.; Toyat, Aicher Joseph (2015)
The famous Adan Rice or popularly known as Bario Rice is grown mainly in Bario and Ba’Kelalan (Sarawak) and Krayan (Indonesia) at elevation range from 450 m a.s.l to 1100 m a.s.l. Paddy cultivation system in these areas is based on rainfed and utilizing low fertilizer input which resemble nature farming. This is a signature rice for Sarawak and it is a must as a souvenir among local tourists visiting the Highlands. Traditional or nature farming system practices do not use any machineries and cultivation is done manually with the help of buffaloes. Tillage and manuring is accomplished with buffaloes grazing within the paddy field and kept to fallow 4-5 months before the next planting season. The objectives of this study are to determine the yield and soil health status of the paddy field in Ba’kelalan and the potential of increasing rice yield by utilizing locally available resources with minimal application of NPK fertilizer. Total of 30 paddy fields had been randomly selected where soil samples and yield were measured by having 3 plots of 1m2 quadrats in each paddy field. Fertilizer effectiveness trial was done insitu to determine the response of the Adan Halus towards fertilizer. In adopting this method, the average Total Carbon (TC) before the planting season were 5.36 % (at 0-15cm depth) and 4.79% (at 15-30cm depth), with Organic Matter (OM) of 15.75% (0-15cm depth) and 14.20% (at 15-30cm depth). The average pHKCl was 3.85 to 4.09 for the paddy fields and CEC value range from 10 cmol kg-1 to 19.35 cmol kg-1. The yield of paddy harvested ranged from 0.5 t to 9 t ha-1 and aboveground biomass (paddy straw) at an average of 17.07 t ha-1 (fresh weight). Preliminary agronomic yield improvement study conducted in Ba’kelalan showed that the Adan Halus has the potential to produce up to 6 t ha-1 of paddy per season with 36.67 t ha-1 of paddy straw. Application of NPK 17.5:15.5:10 at 240 kg ha-1 and biochar at 5 t ha-1 effectively increased the yield of Adan Halus to 6 t ha-1.